A case of severe COVID-19 and influenza co-infection - Riabokon, O. V.; Furyk, O. O.; Kalashnyk, K. V.; Рябоконь, Олена Вячеславівна; Фурик, Олена Олександрівна; Калашник, Кирило Вадимович (Запорізький державний медико-фармацевтичний університет, 2023)
Aim. To analyze a case of severe COVID-19 and influenza co-infection in a 48-year-old female patient. Materials and methods. The clinical course, specifics of diagnosis and therapy of the 48-year-old patient S., who was treated for severe co-infection of COVID-19 and influenza at Municipal non-profit Enterprise “Regional Infectious Clinical Hospital” Zaporizhzhіa Regional Council from 29.01.2023 to 17.02.2023, were analyzed. The diagnosis of COVID-19 was confirmed by the detection of SARS-CoV-2 Ag in nasopharyngeal swabs by the immunochromatographic method, and the diagnosis of influenza – by the influenza A viral RNA detection by the polymerase chain reaction method. Current regulatory documents were used when examining and treating the patient. Results. It has been recognized that the unvaccinated 48-year-old female patient was at a risk group due to comorbid pathology (stage 2 hypertension, type 2 diabetes mellitus, grade 2 obesity) developed a severe course of COVID-19 and influenza type A co-infection. The course of co-infection was complicated by severe acute respiratory distress syndrome already on the 6th day of the disease. The diagnosis of COVID-19 was confirmed by a rapid SARS-CoV-2 antigen test. Treatment for COVID-19 was started immediately with the use of remdesivir, dexamethasone, and anticoagulants. However, despite the patient was given the treatment, his condition worsened due to the rapid progression of acute respiratory failure. The presence of clear clinical and laboratory signs of “cytokine storm” required the use of tocilizumab on the 7th day of the disease. Oseltamivir was commenced after receiving laboratory confirmation of influenza A by the PCR method on the 8th day of the disease. A complete etiologic interpretation of the diagnosis made it possible to prescribe a combination antiviral treatment which coupled with the timely additional initiation of tocilizumab, allowed obtaining certain positive dynamics after only five days of treatment with further improvement of the patient’s condition. Мета роботи – проаналізувати випадок тяжкого перебігу ко-інфекції COVID-19 і грип у пацієнтки віком 48 років. Матеріали та методи. Проаналізували клінічний перебіг, особливості діагностики та лікування хворої С. Віком 48 років, яка перебувала на стаціонарному лікуванні в КНП «Обласна інфекційна клінічна лікарня» ЗОР у період з 29.01.2023 р. до 17.02.2023 р. з приводу тяжкого перебігу ко-інфекції COVID-19 та грип. Діагноз COVID-19 підтверджено виділенням у носоглотковому слизу Ag SARS-CoV-2 імунохроматографічним методом, а діагноз грип – виділенням РНК вірусу грипу тип А методом полімеразної ланцюгової реакції. Під час обстеження та лікування пацієнтки дотримувалися чинних нормативних документів. Результати. У невакцинованої пацієнтки віком 48 років, яка належить до групи ризику внаслідок наявності коморбідної патології (гіпертонічна хвороба 2 ст., цукровий діабет 2 типу, ожиріння 2 ст.), розвинувся тяжкий перебіг ко-інфекції COVID-19 та грип А, що ускладнилася тяжким гострим респіраторним дистрес-синдромом уже на 6 день хвороби. Діагноз COVID-19 підтверджено швидким тестом на виявлення Ag SARS-CoV-2, тому одразу почали лікування COVID-19, призначивши ремдесивір, дексаметазон, антикоагулянти. Втім, на тлі терапії стан хворої погіршився – спостерігали швидке прогресування гострої дихальної недостатності. Чіткі клініко-лабораторні ознаки «цитокінового шторму» зумовили необхідність призначити тоцилізумаб на 7 добу хвороби. Лабораторне підтвердження грипу А методом ПЛР на 8 добу хвороби спричинило призначення осельтамивіру. Повне етіологічне розшифрування діагнозу дало змогу призначити комбіноване противірусне лікування, що в поєднанні з своєчасним додаванням до терапії тоцилізумабу сприяло позитивній динаміці вже через п’ять діб лікування з наступним поліпшенням стану пацієнтки.
Випадок важкої ко-інфекції COVID-19 і грипу
Riabokon O. V. - ORCID ID: 0000-0002-7394-4649; Furyk O. O. - ORCID ID: 0000-0002-5196-7698; Kalashnyk K. V. - ORCID ID: 0000-0002-4532-8953.
Keywords: coronavirus disease COVID-19; influenza; viral infection; co-infection; clinic; complications; diagnosis; comorbidity; risk factors; treatment; коронавірусна хвороба COVID-19; грип; вірусна інфекція; ко- інфекція; клініка; ускладнення; діагностика; коморбідність; фактори ризику; лікування